(untitled) (Revista Apotheke, 2024)
This article presents reflections on the conception of “home” of children and adolescents who live in Ocupação Justo, in São Leopoldo, considering visual arts as an instrument for redefining social identity within the inhabited context. The field research was carried out between the months of October and November 2023, with a group of approximately 40 children and adolescents, between 7 and 17 years old, participating in the Tenda do Encontro, the Ocupação’s space for activities with the community. Based on the work carried out in the meetings, we sought to analyze the impact of art/education workshops, in order to capture and transmit the narratives underlying these occupied spaces, to become aware of the context in which they live, giving new meaning to the feeling of social belonging of the residents of that region. The practices involved the presentation of people and projects that address the houses and the feelings promoted by them, expressing their identities and the feeling of belonging, reflecting stories and realities of the occupation, they are: Marcelino Melo (Quebradinha Project), the Morrinho Project ( RJ), visual artist Mônica Nador (JAMAC Project), the African festival Bogo Ja and the Yanomami village-house. The theoretical framework that underlies the reflection included Walter Benjamin, Ana Mae Barbosa, Georges Henri Luquet and Gaston Bachelard. Reflection on the research carried out shows that young people use art education as a refuge to do what they like, in addition to having Ocupação Justo as an extension of their own homes. Furthermore, the group participating in the research demonstrated a new meaning regarding the perception of their homes, their Occupation and the context in which they live, revealing that art has an essential role in the construction of identities and its presence is essential in non-school education spaces.